2010
DOI: 10.1111/j.1468-5957.2010.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Informed Investors and the Internet

Abstract: During the last decade the Internet has become an increasingly important source for gathering company related information. We employ Wikipedia editing frequency as an instrument that captures the degree in which the population is engaged with the processing of company-related information. We find that firms whose information is processed by the population more frequently are associated with lower analysts' forecast errors, smaller analysts' forecast dispersions, and significant changes in bid-ask spreads on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
1
34
0
6
Order By: Relevance
“…Some studies (Hu et al, 2011;Rubin & Rubin, 2010;Drake et al, 2012;Blankespoor et al, 2014) sought to relate the use of social networks with information asymmetry and the pricing of shares.…”
Section: Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Some studies (Hu et al, 2011;Rubin & Rubin, 2010;Drake et al, 2012;Blankespoor et al, 2014) sought to relate the use of social networks with information asymmetry and the pricing of shares.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Rubin and Rubin (2010) employed the frequency of editing in Wikipedia as an instrument that captures the extent of the population's involvement in the processing of information related to companies. The results obtained indicated that, for investors and analysts to be informed about companies, processing of information via the internet should be related to the extent of the population's involvement.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A internet tem se tornado cada vez mais uma importante fonte para coleta de informações sobre as empresas, e a sua utilização faz com que os indivíduos estejam mais bem informados em vários campos do cotidiano (RUBIN; RUBIN, 2010). Bogan (2008) mostrou que um aumento na presença de computadores e a utilização da internet têm efeito substancial sobre o mercado financeiro, devido ao aumento no nível de participação das famílias no mercado de capitais.…”
Section: Desenvolvimento Das Hipóteses E Testes Utilizadosunclassified
“…Essas alterações na forma de transmitir a informação, também afetaram a divulgação, compulsória ou voluntária, das informações contábeis das empresas. Atualmente, com a crescente necessidade dos investidores em possuir maior volume de informações sobre as empresas, as redes sociais se tornam uma influente ferramenta para a captação de informações, tendo, assim, potencial para reduzir a assimetria informacional entre a empresa e seus investidores (RUBIN; RUBIN, 2010).…”
Section: Introductionunclassified